THE EUROPEAN UNION ON THE WAY TO THE UNIFORM DIGITAL MARKET - NIKOLAY SERGEEVICH Revenko (Мир новой экономики)
The article reviews measures aimed at creating the EU Single Digital Market (SDM) envisaged by the relevant Strategy. The Strategy appearance stems from the rapid development of Information and Communication Technology (ICT) and existence of several barriers that impede expansion of cross-border trade of goods and services. The SDM creation is carried out within three pillars: better access for consumers and businesses to online goods and services across Europe, creating the right conditions for digital networks andservices to flourish and maximising the growth potential of the European Digital Economy. The final SDMgoals are building of data economy and society that offers equal opportunities to all, stimulation of cross-border trade and services, enhancement of EU economy competitiveness. Some plans envisaged by the Strategy were implemented in 2015, inter alia, the European Commission submitted its proposals on expending access of consumers to digital content while travelling abroad and on the personal data protection. The Strategy implementation is going on.